2017
DOI: 10.1371/journal.ppat.1006269
|View full text |Cite
|
Sign up to set email alerts
|

Neisseria gonorrhoeae infects the human endocervix by activating non-muscle myosin II-mediated epithelial exfoliation

Abstract: Colonization and disruption of the epithelium is a major infection mechanism of mucosal pathogens. The epithelium counteracts infection by exfoliating damaged cells while maintaining the mucosal barrier function. The sexually transmitted bacterium Neisseria gonorrhoeae (GC) infects the female reproductive tract primarily from the endocervix, causing gonorrhea. However, the mechanism by which GC overcome the mucosal barrier remains elusive. Using a new human tissue model, we demonstrate that GC can penetrate in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
63
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(65 citation statements)
references
References 86 publications
2
63
0
Order By: Relevance
“…GC aggregation has been observed in patient biopsies and exudates where GC aggregates were found on ectocervical epithelium from displaying cervicitis and phagocytic immune cells from patients displaying urethritis [ 18 , 19 ]. Our ex vivo infection study using endocervical tissue explants found GC aggregates on the endocervical epithelium and GC biofilm on the ectocervical epithelium [ 20 , 21 ]. We also noticed that GC form aggregates not only on the surface of epithelium but also on exfoliated cervical epithelial cells even in the absence of Opa or pili expression (data not shown), suggesting the presence of unknown host factors that facilitate GC aggregation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GC aggregation has been observed in patient biopsies and exudates where GC aggregates were found on ectocervical epithelium from displaying cervicitis and phagocytic immune cells from patients displaying urethritis [ 18 , 19 ]. Our ex vivo infection study using endocervical tissue explants found GC aggregates on the endocervical epithelium and GC biofilm on the ectocervical epithelium [ 20 , 21 ]. We also noticed that GC form aggregates not only on the surface of epithelium but also on exfoliated cervical epithelial cells even in the absence of Opa or pili expression (data not shown), suggesting the presence of unknown host factors that facilitate GC aggregation.…”
Section: Discussionmentioning
confidence: 99%
“…GC aggregation and adherence to host cells through these molecules may influence each other, therefore changing both the infectivity and antibiotic resistance of GC in the reproductive tract of women. Indeed, we have previously shown that Opa expression facilitates GC adherence to host cells and GC aggregation, but reduces GC penetration into both polarized epithelial cell monolayers and the endocervical epithelium in the tissue explant model [ 16 , 20 ]. The functions of Opa in both GC-GC and GC-epithelial interactions enable Opa-expressing GC to survive better in the presence of antibiotic agents and dominate the colonization of the epithelial surface.…”
Section: Discussionmentioning
confidence: 99%
“…GC also disrupt the apical junctions of polarized HEC-1-B (endometrial) and T84 (colonic epithelial) cells by activating epidermal growth factor receptor (EGFR) signaling (which also involves redistribution of β-catenin) ( 61 ). The disassembly of apical junctions is also seen in an endocervical tissue model of infection, where GC activates intracellular non-muscle myosin II and induces calcium flux to promote the exfoliation of columnar epithelial cells ( 62 ). Additional investigation is needed into the composition of cellular junctions between ciliated and non-ciliated fallopian tube epithelial cells, the activity of bacterially-induced MMPs, and the intracellular signaling pathways activated by gonococci to determine what factors make ciliated cells especially sensitive to exfoliation.…”
Section: Invading the Fallopian Tubementioning
confidence: 99%
“…Wang et al 2 used an ex vivo human tissue model to demonstrate that NG causes epithelial shedding by apical junction breakdown, increasing NG penetration into the endocervix. This process requires activation of non-muscle myosin II at the NG adherent sites and apical surface, triggered by NG inoculation.…”
Section: Mechanisms Of Neisseria Gonorrhoeae Infectionmentioning
confidence: 99%